2009
DOI: 10.1007/s00441-009-0870-2
|View full text |Cite
|
Sign up to set email alerts
|

Macroglial cells of the teleost central nervous system: a survey of the main types

Abstract: Following our previous review of teleost microglia, we focus here on the morphological and histochemical features of the three principal macroglia types in the teleost central nervous system (ependymal cells, astrocyte-like cells/radial glia and oligodendrocytes). This review is concerned with recent literature and not only provides insights into the various individual aspects of the different types of macroglial cells plus a comparison with mammalian glia, but also indicates the several potentials that the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 84 publications
2
26
0
2
Order By: Relevance
“…The present data suggests that in the trout telencephalon CBS may label aNSCs with a glial phenotype (radial glia). Our assumption is consistent with the results of studies of the pallial neurogenic niche in adult zebrafish containing radial glia-like aNSCs with cellular bodies lining the walls of the ventricle [19]. Studies of the hydrogen sulfide biology in the mammalian brain have shown that astrocytes and glial cells constitute the main repositories of CBS in the brain [3].…”
Section: Telencephalonsupporting
confidence: 90%
“…The present data suggests that in the trout telencephalon CBS may label aNSCs with a glial phenotype (radial glia). Our assumption is consistent with the results of studies of the pallial neurogenic niche in adult zebrafish containing radial glia-like aNSCs with cellular bodies lining the walls of the ventricle [19]. Studies of the hydrogen sulfide biology in the mammalian brain have shown that astrocytes and glial cells constitute the main repositories of CBS in the brain [3].…”
Section: Telencephalonsupporting
confidence: 90%
“…12 The macroglial cells of the CNS include astrocytes, ependymal cells, and radial cells. 13 Astrocytes, which are also called "astroglia," connect the neurons to the blood vessels and may be an important part of the blood-brain barrier, control the extraneural space by removing ions and recycling neurotransmitters, and may also be involved in the regulation of vasodilatation and vasoconstriction. 10 Oligodendrocytes coat the axons such as the optic nerve fibers with myelin as electrical insulation.…”
Section: Microgliamentioning
confidence: 99%
“…, 2009). In fish, however, radial glia is the predominant glia type (Cuoghi & Mola, 2009) and retains its neurogenic function in adulthood. It is therefore of interest to explore whether also radial glia undergoes gliosis as function of age.…”
Section: Introductionmentioning
confidence: 99%